The Elements of Social Theory. - Barnes, Barry (Princeton legacy library., 2014)
Over the past quarter century, social theory has moved in diverse and often seemingly incompatible directions, exaggerating differences of approach that existed even in earlier periods. In a strikingly original book, Barry Barnes uses this intellectual diversity not only to identify but also to unify the central ways of looking at the field. Barnes frames his task by addressing the most important problem confronting all students of society today: the apparent conflict between cultural and functional methods of describing the social order, on one hand, and choice-theoretic accounts, on the o.